2015
DOI: 10.1002/elan.201500604
|View full text |Cite
|
Sign up to set email alerts
|

Nonenzymatic Electrochemical Biosensor Based on Novel Hydrophilic Ferrocene‐terminated Hyperbranched Polymer and its Application in Glucose Detection

Abstract: We designed a novel water soluble topological structure polymer‐ferrocene‐ terminated hyperbranched polyurethane (HPU‐Fc) with good water solubility. The redox behaviors and the electrochemical kinetics parameters of HPU‐Fcs were explored by cyclic voltammetry (CV) according to electrochemical principle. The topological structure polymer was applied for the design and engineering of non‐enzymatic glucose sensor. The designed sensor showed good response to glucose concentration with good stability, favorable ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 41 publications
0
12
0
Order By: Relevance
“…This is especially critical, when considering the study of Li et al. showing an abiotic sensor for glucose being only based on platinum modified with polymer‐functionalized ferrocene …”
Section: Resultsmentioning
confidence: 84%
“…This is especially critical, when considering the study of Li et al. showing an abiotic sensor for glucose being only based on platinum modified with polymer‐functionalized ferrocene …”
Section: Resultsmentioning
confidence: 84%
“…Ferrocene and ferrocene derivatives have been focused on attributed to their unique applications such as electrochemistry, 10 biosensors, 10–11 molecular recognition, 11–12 catalysis, 13–14 fertilizers, 15 magnetism, 16 cancer treatment 17 and others 18–19 . Especially, ferrocene‐bearing polymers were of interest in the excellent combination of redox, mechanical, semi‐conductive, photo‐physical, and opto‐electronic properties 11,20–21 .…”
Section: Introductionmentioning
confidence: 99%
“…Using portable electronic devices to directly detect glucose is a convenient diagnostic method in the initial steps. A literature survey found that glucose sensors can be divided into two categories: enzyme-based sensors [ 5 , 6 ] and enzyme-free sensors [ 7 , 8 ]. Enzyme-based electrochemical biosensors are complex, expensive and affected by temperature and pH due to enzyme activity.…”
Section: Introductionmentioning
confidence: 99%